2011
DOI: 10.1039/c1pp05165b
|View full text |Cite
|
Sign up to set email alerts
|

Fluorescence of methylated derivatives of hydroxyphenylimidazopyridine. Resolution of strongly overlapping spectra and a new ESIPT dye showing very efficient radiationless deactivation

Abstract: The ground- and excited-state behaviour of the isomeric species 2-(2'-methoxyphenyl)imidazo[4,5-b]pyridine (1-OMe) and 2-(2'-hydroxyphenyl)-4-methylimidazo[4,5-b]pyridine (1-NMe) in neutral and acid media has been studied by UV-vis absorption spectroscopy, steady-state and time-resolved fluorescence spectroscopy. The new dye 1-NMe is non-fluorescent in neutral media except in trifluoroethanol, where it shows a very weak fluorescence. 1-NMe also exhibits highly solvent-dependent fluorescence intensity in acidic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
55
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(61 citation statements)
references
References 86 publications
6
55
0
Order By: Relevance
“…Rodríguez et al . elaborated that when the electron withdrawing ability of the imidazopyridine ring increases the quantum yield of the tautomer emission of HPIP‐b decreases . Same way it was shown that the substitution of electron donating diethylamino group on the phenolic ring reduces the fluorescence of HPBI .…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…Rodríguez et al . elaborated that when the electron withdrawing ability of the imidazopyridine ring increases the quantum yield of the tautomer emission of HPIP‐b decreases . Same way it was shown that the substitution of electron donating diethylamino group on the phenolic ring reduces the fluorescence of HPBI .…”
Section: Resultsmentioning
confidence: 94%
“…More recently, Rodríguez et al . showed that the deprotonation of the hydroxyl group (increasing the charge on the donor moiety) or protonation/methylation on the pyridyl nitrogen of HPIP‐b (increasing the electron withdrawing ability of the acceptor group) enhances the radiationless deactivation of HPIP‐b .…”
Section: Introductionmentioning
confidence: 97%
“…A similar TICT process has been reported for the tautomer of various HPIP-related hydroxyarylbenzazoles. [25,29,33,34] As shown in Figure 2, the value of the ratio SR for HPIP is highly sensitive to the environment of the dye. In aqueous medium, the spectral ratio SR has a value of approximately 0.3, which drops abruptly with the addition of a small percentage of ethanol.…”
Section: Photophysical Behavior Of Hpip In Physiologically Relevant Amentioning
confidence: 99%
“…The red shifted keto emission in ESIPT process is mainly attributed to the four level cyclic proton transfer reaction (E →E*→K*→K→E) which completes after the reverse proton transfer from the keto form (K) to the original enol form (E) in the ground state. Hence variety of ESIPT chromophores e. g. 2‐(benzo[d]thiazol‐2‐yl)phenol (HBT) 2‐(benzo[d]oxazol‐2‐yl)phenol (HBO), 2‐(1H‐benzo[d]imidazol‐2‐yl)phenol (HBI), oxadiazole, 3‐hydroxyflavone(3HF), 3‐hydroxychromones, hydroxyl phenyl imidazole (HPI), imidazopyridine methyl salicylate have been extensively studied for their…”
Section: Introductionmentioning
confidence: 99%